Influence of Listeria monocytogenes and environmental abiotic factors on growth parameters and aflatoxin B1 production by Aspergillus flavus. (January 2015) - Asurmendi, P.; Barberis, C.; Pascual, L.; Dalcero, A.; Barberis, L.
Abstract: Aspergillus flavus growth is influenced by a variety of abiotic factors including water activity ( a W ), pH, redox potential, relative humidity, temperature and availability of oxygen. Furthermore, biotic factors such as the presence in the same habitat of different microorganisms can develop ecological interactions between them that are positive, negative or indifferent for fungal growth. The aim of the present work was evaluate the effect of Listeria monocytogenes in interaction with a W, pH and temperature on the lag phase, growth rate and AFB1 production of A. flavus . Ecophysiological in vitro studies of A. flavus demonstrate that the co-occurrence with L. monocytogenes in culture medium and abiotic factors ( a W, pH and temperature) influence the growth of the fungal strains and the production of AFB1 . The presence of L. monocytogenes generally decreased fungal growth and increased significantly aflatoxin production. These studies are essential in the prediction of contamination risk of food with these microorganisms or their toxins in interaction with several environmental parameters. Highlights: Fungal lag phase in presence of Listeria monocytogenes were generally longer than controls. The lowest growth rate of AF21 and AF54 were observed in presence of Listeria. The bacteria stimulated aflatoxin synthesis.